PERAN BUDAYA MAPALUS TERHADAP PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI KELURAHAN PANGOLOMBIAN TOMOHON SULAWESI UTARA - Rumengan, Yusufian Magdalena; Sampul, Syalom (Yayasan Syalom Cipta Sumikolah, 2024)
Humans arebthe most noble of God’s creatures among God’s other creatures. Every human being in their daily life definitely and will always need other humans for their survival. Mapalus are shared values and practices for a common goal that live and move in the Tou Minahasa civilization. The culture of the Mapalus tribe as aform of modern mutual cooperation for example associations or socializatioan of Mapalus bussines is the basic essence and life activies of Minahasa people who are called to basic sincerity of conscience and exploring Mapalus with full awareness and responsibility enables humans and their groups to mutually revive and prosper each person and group in their community. Mapalus is often used as a community organization in Minahasa, mapalus is basses on kinship religion and the unity and integrity of mapalus, including mapalus of farmers, fishermen, money mapalus of grief and marriage as well as mapalus communitygroups. The research found that even though the Mopalus/Mapalus culture has begin to diminish, the Mopalus/ Mapalus cuture and spirit will not disappear in the lives of the people of Pangolombian Village because there are principles and values in it that animate Mopalus/Mapalu.